The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1016/j.envsci.2011.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Traffic impacts on PM2.5 air quality in Nairobi, Kenya

Abstract: Motor vehicle traffic is an important source of particulate pollution in cities of the developing world, where rapid growth, coupled with a lack of effective transport and land use planning, may result in harmful levels of fine particles (PM2.5) in the air. However, a lack of air monitoring data hinders health impact assessments and the development of transportation and land use policies that could reduce health burdens due to outdoor air pollution. To address this important need, a study of traffic-related PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(86 citation statements)
references
References 30 publications
6
74
2
Order By: Relevance
“…The location of monitoring station with respect to the adjacent road has been found to be a main factor affecting the PM concentrations at classroom B. When compared with previous studies, it was found that in most of the outdoor measurements, the PM concentrations showed sharp drop with distance away from roadway (Kinney et al, 2011;Levy et al, 2003). Kinney et al (2011) observed that the average concentrations at the roadside (0 m) were more than 4 times higher than average concentrations 30 m away, and over 6 times higher than those 100 m away.…”
Section: Spatial Variations In Pm Concentrationsmentioning
confidence: 76%
See 1 more Smart Citation
“…The location of monitoring station with respect to the adjacent road has been found to be a main factor affecting the PM concentrations at classroom B. When compared with previous studies, it was found that in most of the outdoor measurements, the PM concentrations showed sharp drop with distance away from roadway (Kinney et al, 2011;Levy et al, 2003). Kinney et al (2011) observed that the average concentrations at the roadside (0 m) were more than 4 times higher than average concentrations 30 m away, and over 6 times higher than those 100 m away.…”
Section: Spatial Variations In Pm Concentrationsmentioning
confidence: 76%
“…When compared with previous studies, it was found that in most of the outdoor measurements, the PM concentrations showed sharp drop with distance away from roadway (Kinney et al, 2011;Levy et al, 2003). Kinney et al (2011) observed that the average concentrations at the roadside (0 m) were more than 4 times higher than average concentrations 30 m away, and over 6 times higher than those 100 m away. A Student's t test (single-tailed) was also performed to determine whether the PM 10 , PM 2.5 , and PM 1 concentrations were significantly higher at near-field region compared with far-field region.…”
Section: Spatial Variations In Pm Concentrationsmentioning
confidence: 77%
“…Using the deposition fractions from fine PM, the estimated deposited masses are 9.5 µg in the head airways region, 1.1 µg in the tracheobronchial region and 0.7 µg in the pulmonary for every 1000 L of air breathed by an average urbanite in Nairobi city. However, Kinney et al (2011) reported PM 2.5 average concentration of 98.1 µg m -3 from a sidewalk in the Central Business District which translates to a deposition of 45 µg (head airways), 5.2 µg (tracheobronchial) and 3.0 µg (pulmonary). A study on occupational exposure by Ngo et al (2015) reported that bus drivers in Nairobi city were exposed to about 103 µg m -3 which translates to a deposition of 46 µg to the head airways, 5.5 µg to the tracheobronchial and 3.2 µg to the pulmonary tract.…”
Section: Discussionmentioning
confidence: 99%
“…The urban centres in Africa are growing at exceedingly high rates whereas the provision of prerequisite social services and amenities are not commensurate with this growth (UN-HABITAT, 2006;UNDESA, 2010;Karanja and Makau, 2012). The urban population is reported to be exposed to wide range of air pollutants (Gulis et al, 2004;Ngo et al, 2015) whose sources have been identified as vehicular emissions, biomass burning and mineral dust (Formenti et al, 2003;Gatari and Boman, 2003;Kinney et al, 2011;Petkova et al, 2013;Gaita et al, 2014). Therefore, the objectives of this study were to obtain a size distribution of PM and elemental concentrations in a typical African city and to determine the deposition fractions of measured PM and trace elements in the respiratory system.…”
Section: Introductionmentioning
confidence: 99%
“…Toxic gases such as CO, NO x , SO x and PM x are in high concentrations as a result of increased urban expansion and motorization linked to rapid economic development experienced over the last decade. Consequently, most city residents are exposed to elevated concentrations of vehicular emissions that potentially pose serious long-term eff ects on human health and quality of the urban environment (Odhiambo et al, 2010;Kinney et al, 2011;Vliet & Kinney, 2007). For instance, CO causes blood clotting when it reacts with haemoglobin.…”
Section: Introductionmentioning
confidence: 99%